Virginity, purity and honour: Theology in Luke 1:46-55 and Nias bridal culture - Ibelala Gea (HTS Teologiese Studies/Theological Studies)
This article is motivated by the election of Mary, who was unmarried and still a virgin, to be the mother of Jesus the Saviour. This study aims to reveal the reasons for the election of Mary by conducting a theological analysis of the text of Luke 1:46–55 and then implied in the culture of carrying brides of the Nias tribe. This study uses a qualitative method by reading literature, books, journals and relevant references. Based on the study’s results, purity is the main requirement, according to culture and theology. Mary, the mother of Jesus, is worthy of being on the path of the incarnation of the holy God. Purity as a prerequisite also applies in the local wisdom of the Nias people, namely carrying brides as a symbol of respect and glory but only for those who maintain their purity until marriage. For that reason, this culture needs to be preserved as a motivation in maintaining the moral values and sanctity of the lives of unmarried women amidst the foreign cultural phenomenon related to premarital sex freedom. The resulting positive impact is that virgin women, when married, are treated with honour and dignity.